(untitled) (Comparative Professional Pedagogy, 2021)
Approaches to the professional development of teachers in foreign countries are analyzed. Analysis of the experience of world countries has shown that both public schools and specialized institutions/leading academies and private companies make a significant contribution to the continuous, professional development of teachers, their self-education and professional development. It is emphasized that the professional development of different countries has its own characteristics, is constantly being transformed, taking into account modern needs. Various forms of education, innovative methods, programs, projects, courses are emphased on. In Finland, teacher training is provided through special programs, school-based project activities, international cooperation projects and national research programs. The training is organized by the National Education Agency of Finland. In the UK, a teacher must take an 18-day (30-hour) training each year. Teachers can choose courses offered at universities, independent counseling centers, education departments, teacher training centers, local education authorities, schools. In France, advanced training is provided by various postgraduate education institutions, university institutes and regional education centers. The professional development of German teachers is based on two main factors: professional development and additional training. In China, self-study and teacher training courses are provided on the basis of educational institutions and envisage an accumulative credit system. Continuing education of Singapore teachers is provided by the National Institute of Education several times during their professional careers. The state financially stimulates the professional development of teachers.